QuantiFERON TB‐gold conversion rate among psoriasis patients under biologics: a 9‐year retrospective study. (29th September 2020) - Megna, Matteo; Ferrillo, Maria; Ruggiero, Angelo; Cinelli, Eleonora; Gallo, Lucia; Fabbrocini, Gabriella
Abstract: Background: Tuberculosis (TB) screening is mandatory for psoriasis biologic treatment. However, evidences regarding TB screening results during biologic treatment are conflicting. Objectives: The aim of this study is to evaluate the rate of QuantiFERON TB Gold test (QFT) conversion in psoriasis patients during biologics over time. Methods: A 9‐year single center retrospective study was performed in order to evaluate the rate of QFT conversion in patients affected by moderate‐to‐severe plaque psoriasis under available biological therapies (anti‐TNF‐α, IL‐12/23, IL‐17). For each patient, demographic data, age, gender, comorbidities, previous psoriasis therapy, as well as ongoing treatment type were registered. Five‐hundred twenty‐six patients (61.2% male, with a mean age of 52.6 ± 13.9 years) treated with biologics were enrolled. Results: QFT conversion occurred in 6.5% of patients over a mean treatment duration of 3.2 years. On average, QFT conversion occurred after 34.05 months of treatment. Anti‐TNF‐α drugs, and among them, adalimumab above all (35.5% of all cases), were the most commonly involved treatment during QFT conversion, followed by anti‐IL‐12/23 (17.6%) and anti‐IL‐17 (14.7%). However, differences among biologics class or single biologics (adalimumab, etanercept, infliximab, golimumab, certolizumab, ustekinumab, ixekizumab, secukinumab) did not approach statistical significance. Conclusions: Annual TB screening is important in psoriasis patients under biologic treatment in order to avoid possible latent TB infection reactivation. Indeed, our data showed that even in a low TB prevalence country like Italy, QFT may convert over time in psoriasis patients under biologics in 6.5% of the cases.